2003
DOI: 10.1002/ajmg.a.20248
|View full text |Cite
|
Sign up to set email alerts
|

Left‐sided CHILD syndrome caused by a nonsense mutation in the NSDHL gene

Abstract: Congenital hemidysplasia with ichthyosiform nevus and limb defects (CHILD) syndrome is a rare X-linked dominant malformation syndrome characterized by unilaterally distributed ichthyosiform nevi, often sharply delimited at the midline, and ipsilateral limb defects. At least two-thirds of cases demonstrate involvement of the right side. Mutations in an essential enzyme of cholesterol biosynthesis, NAD(P)H steroid dehydrogenase-like [NSDHL], have been reported in five unrelated patients with right-sided CHILD sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Alopecia may occur, usually on the more involved side, and nails are often dystrophic. Involvement of the right side of the body is more common than the left, although visceral involvement occurs more frequently in left-sided cases ( 258,263 ).…”
Section: Gene Identifi Cation and Molecular Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Alopecia may occur, usually on the more involved side, and nails are often dystrophic. Involvement of the right side of the body is more common than the left, although visceral involvement occurs more frequently in left-sided cases ( 258,263 ).…”
Section: Gene Identifi Cation and Molecular Biologymentioning
confidence: 99%
“…Although CHILD Syndrome results from a cholesterol biosynthetic enzyme defi ciency, cholesterol levels in plasma from affected females are normal, and abnormal metabolites may be diffi cult to detect ( 263 ). Indeed, in Nsdhl deficient female mice, plasma sterol profi les are normal.…”
Section: Sterol Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Hummel et al 10 reported nonsense mutation E151X on exon 5, and Murata et al 11 have reported another mutation, Y349C on exon 8 of the NSDHL gene. Although none of the reported exon 4 and 6 mutations are detected in our VX cases, the occurrence of a mutation in the NSDHL gene, along with morphological similarities in the skin lesions of CHILD syndrome and VX, supports the functional role of this gene in the pathogenesis of VX.…”
Section: Commentmentioning
confidence: 99%
“…1,10,11,17,18 Evaluation for HPV in VX has been studied and has included types 6, 7, 11, 12, 16 to 19, 31, 33, 35, 37, 44 to 47, 53, 54, and 58. 6,13,[21][22][23] While most studies failed to show evidence of HPV, 1 study 13 demonstrated by immunohistochemical analysis a positive reaction in the upper epidermal keratinocytes, which was confirmed by electron microscopy and by PCR, which also detected HPV-DNA 6a.…”
Section: Commentmentioning
confidence: 99%